Helminths infecting the Carvalho’s escuerzo Odontophrynus Carvalhoi from the brazilian state of ceará - Feitosa Quirino, Tatiana (2023)
The family Odontophrynidae comprises 40 anuran species widely distributed in South America, ranging from Brazil to Argentina and Paraguay. Odontophrynus carvalhoi Savage and Cei, 1965, a medium-sized species with terrestrial habits and explosive reproduction, is one of the representatives of this family. Despite its extensive distribution, data regarding its natural history are limited, with published information primarily focused on activity patterns, diet, and defensive behavior. In this study, we present data on the composition and infection patterns of endoparasites associated with O. carvalhoi in a relictual forest in the Brazilian state of Ceará. The parasite community comprised 11 species, with Aplectana hylambatis (76.67%) and Oswaldocruzia mazzai (79.49%) being the most prevalent. Additionally, we report new occurrences of parasite species for O. carvalhoi, contributing to the understanding of the parasitic fauna in the Neotropical region. These findings underscore the importance of parasitological research for a comprehensive understanding of the ecology and biology of this amphibian species.